Tuberculous mastitis: a rare case report - Ennasser, Hind; Raoudi, Jamal Eddine; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Tuberculous mastitis is a granulomatous mastitis due to infection by mycobacterium tuberculosis. It’s a rare entity witch is often confused with breast carcinoma or pyogenic breast abscess because of its clinical and radiological aspect. The diagnosis is histological with identification of an epithelioid cell granulomas and necrosis. The treatment is based on anti-tuberculous therapy with a good clinical issue. Authors report a case of tubercular mastitis in a post-menopausal female diagnosed on adenectomy.